Hak Cipta atas Hasil Tulisan Kecerdasan Artifisial: Tinjauan Etika Kekayaan Intelektual dan Status Kepemilikannya - Karimullah, Muhammad Zidan; Putri, Ria Wierma; Rohaini, Rohaini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Artificial Intelligence (AI) technology has ushered the world into a new era in which machines exhibit certain aspects of human intelligence. One such capability of AI is its ability to generate written responses based on commands or inquiries posed by humans, facilitated by natural language processing (NLP). This output raises legal concerns regarding copyright ownership and the ethical considerations surrounding intellectual property. This research examines the ethical dimensions of intellectual property in relation to AI-generated writing and analyzes the status of copyright ownership for works produced by AI. The study employed a normative legal method, employing statutory, case-based, and conceptual approaches. The data sources included primary, secondary, and tertiary legal sources. The findings indicate that, in its current implementation, AI-generated written works conflict with the ethical values of intellectual property due to the infringement of moral rights associated with copyright (right of attribution and right of integrity). Copyright ownership of AI-generated works for outputs that do not meet this standard, ownership is classified as public property under the principle of the public domain (open to the public). Consequently, developers and users of AI platforms cannot be regarded as copyright owners, as the requisite originality is absent, and AI, as a machine, cannot be deemed a creator due to the absence of human agency. The legal framework governing AI and its copyright remains inadequately defined under national legislation, resulting in insufficient legal protection against AI utilization. So, regulations regarding artificial intelligence are needed to handle this.